Nanoparticles in biomedical implants: Pioneering progress in healthcare - David Raymond; Induni Nayodhara Weerarathna; John Kessellie Jallah; Praveen Kumar (AIMS Bioengineering)
In the quickly evolving world of healthcare today, new technologies are constantly altering the way we approach medical treatments. Biomedical implants are specialist devices designed to enhance physiological functions. Heart pacemakers and artificial joints are merely a few instances of how they could enhance, assist, or replace different bodily parts. These implants have significantly improved our health and enjoyment of life. In this discipline, nanoparticles are now creating new opportunities. These tiny particles are endowed with extraordinary properties that could improve implant functionality. They can decrease side effects, increase the effectiveness of therapy, and facilitate more harmonious interactions between implants and human bodies. We explored the connection between implants and nanoparticles and showed how both might enhance universal healthcare. This review provides a roadmap for where this technology is headed and how it can help us design safer, more effective implants that enhance people's lives by examining the most recent research and discoveries. It is an intriguing look at healthcare in the future that demonstrates how nanoparticles are reshaping the biomedical implant industry.